Sudden death in infective endocarditis - Castelli, Jussara Bianchi; Almeida, Germana; Siciliano, Rinaldo Focaccia (Autopsy and Case Reports, 2016)
The case fatality rate of infective endocarditis (IE) is high and is associated with varying causes. Among them, acute myocardial infarction due to an embolism in a coronary artery is rare; the incidence of this complication in the setting of IE is reported to be up to 1.5%. We report a case of sudden death in a 22-year-old woman diagnosed with systemic lupus erythematosus who was referred to the Cardiology Center for the treatment of mitral valve incompetence due to IE. She was hemodynamically stable with antibiotic therapy and vasoactive drugs, despite severe mitral valve regurgitation. Unexpectedly, she presented cardiac arrest and died. The autopsy showed total occlusion of the left main coronary artery by septic embolus, which originated from the mitral vegetation, as the cause of death. Thus, although a rare complication, it should always be kept in mind that a coronary embolism can be a lethal complication of IE, and the possibility of surgical treatment combined with the underlying antibiotic therapy should be raised